Linguistic Politeness Analysis in Grade X High School Students’ Negotiation Texts: Pragmatic Perspective and Learning Implications - Atika Zikri; Afnita Afnita; Siti Ainim Liusti (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The purpose of the research is to describe the forms, strategies, and levels of linguistic politeness in the negotiation texts produced by students, as well as to examine their implications for Indonesian language learning. The research method used is qualitative descriptive with a pragmatic approach. The research data consist of 15 negotiation texts written by Grade X students of SMA Negeri 1 West Sumatra, collected through observation, documentation, and simulation of negotiation activities. The analysis was carried out in four stages, namely speech identification, classification of negotiation strategies, analysis of positive and negative linguistic politeness, and formulation of learning implications. The results show that students employed various negotiation strategies, including price bargaining, reasoning, and comparison with other alternatives. Linguistic politeness is reflected in the use of greetings, expressions of requests, expressions of appreciation, and forms of offers that show attention to speech partners. This finding confirms that Indonesian language learning needs to be directed toward strengthening students’ communicative competence. Through the application of the principle of linguistic politeness, it is hoped that polite, effective, and contextual interactions will be fostered.